2021
DOI: 10.1016/j.heliyon.2021.e06907
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection in sinusoidal lid driven cavity with non-uniform temperature distribution on the wall utilizing nanofluid

Abstract: Mixed convection heat transfer of Cu-water nanofluid in an arc cavity with non-uniform heating has been numerically studied. The top flat moving wall is isothermally cooled at Tc and moved with a constant velocity. While the heated arc stationary wall of the cavity is maintained at a hot temperature Th. FORTRAN code is used to solve the mass, momentum, and energy equations in dimensionless form with suitable boundary conditions. In this study, the Reynolds number changed from 1 to 2000, and the Rayleigh number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“… * constant value; remark: if using dimensionless numbers, the ranges are based on common academic proposals in the literature [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… * constant value; remark: if using dimensionless numbers, the ranges are based on common academic proposals in the literature [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. …”
Section: Figurementioning
confidence: 99%
“…A nonlinear influence of nanoparticle concentration on the heat transfer rate for high Reynolds number has been established. Aljabair et al [ 14 ] presented a numerical study of the convective heat and mass transfer of Cu–H 2 O nano-liquid inside an arc chamber with inconsistent heating and a top flat sliding wall. Their findings suggest that the sliding baffle becomes more active to boost heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…A moving boundary of the enclosure enhances the performance of the fluid flow and heat transfer parameters. Many literatures [ 2 , 3 , 4 , 5 , 6 ] investigated fluid flow and heat transfer characteristics for mixed convection problems with differentially heated lid-driven enclosures. Two major types of research works were traced in this regime.…”
Section: Introductionmentioning
confidence: 99%
“…Further enhancement in heat transfer characteristics was achieved by Aljabair et al. [ 5 ] due to the utilization of nanofluid. For the case of sliding side walls of the enclosure, Oztop and Dagtekin [ 6 ] observed that heat transfer enhanced in the natural convection domain for opposing shear and buoyancy forces.…”
Section: Introductionmentioning
confidence: 99%
“…Tey considered Brinkman and Wasp models and suggested heat transfer rate increases for increased Ra and ϕ but diminishes for Ha. Aljabair et al [11] used FORTRAN code to solve mixed convection in a nonuniformly heated arc-shaped cavity. Tey recommended the local and average Nusselt numbers are increasing function of ϕ, Re, and Ra.…”
Section: Introductionmentioning
confidence: 99%